1999
DOI: 10.1002/(sici)1522-7219(199903)8:1<39::aid-icd189>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Maternal verbal interaction in different situations with infants born prematurely or at term

Abstract: The present study investigates whether maternal verbal behaviour, in terms of the use of declaratives, interrogatives and imperatives, can be accounted for by gestational age of the infant, or the situation in which mother–infant pairs were observed. Thirteen mothers and their premature and term babies were observed twice in three situations, namely playing with, feeding and changing their infants. The first observation took place at a mean gestational age of 40 weeks and the second observation took place appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Possibly, the full expression of the mother's touch repertoire may be constrained during feeding, when the mother's hands are occupied in carrying out the task at hand. Although the mother's global style, in terms of sensitivity or intrusiveness, is stable over time (Belsky, Rovine, & Taylor, 1984), the manifestation of maternal sensitivity in the different modalities is often context-dependent (Holditch-Davis, Miles, & Belyea, 2000; Reissland, Shepherd, & Stephenson, 1999). Our findings suggest that feeding and nonfeeding encounters provide important yet distinct contexts for the expression of maternal behavior, and the inclusion of both settings might afford a more comprehensive assessment of the dyadic relationship.…”
Section: Discussionmentioning
confidence: 70%
“…Possibly, the full expression of the mother's touch repertoire may be constrained during feeding, when the mother's hands are occupied in carrying out the task at hand. Although the mother's global style, in terms of sensitivity or intrusiveness, is stable over time (Belsky, Rovine, & Taylor, 1984), the manifestation of maternal sensitivity in the different modalities is often context-dependent (Holditch-Davis, Miles, & Belyea, 2000; Reissland, Shepherd, & Stephenson, 1999). Our findings suggest that feeding and nonfeeding encounters provide important yet distinct contexts for the expression of maternal behavior, and the inclusion of both settings might afford a more comprehensive assessment of the dyadic relationship.…”
Section: Discussionmentioning
confidence: 70%
“…Although mother–preterm infant interactive patterns and their effects on later development have been widely studied, few studies have addressed the analysis of their communicative exchanges and, in particular, maternal verbal input. Findings documented that, at least during the first year of life, maternal speech directed to preterm infants was similar to that addressed to full‐term infants, with respect to its structural features (Reissland et al 1999, Salerni et al 2007). On the contrary, studies that focused on temporal and functional aspects of verbal input highlighted that mothers of preterm children produced more directive and controlling utterances than mothers of term children (Brown et al 1986, Menyuk et al 1995).…”
Section: Introductionmentioning
confidence: 89%
“…In fact, only few studies have focussed on the characteristics of speech directed to premature infants, and the only findings available concern the directivity and the complexity of the maternal linguistic input. More specifically, Reissland, Shepherd & Stephenson (1999), comparing maternal speech directed to term and preterm babies at birth and at 8 weeks, found that gestational age only influences the complexity of maternal interrogative utterances, as measured through the MLU index (mean length of utterance).…”
Section: Introductionmentioning
confidence: 99%